ชีววิทยาการสืบพันธ์ของนกในบริเวณสถานีวิจัย สิ่งแวดล้อมสะแกราช - สายวิเชียร, ปราโมทย์; ทองอารีย์, ศิริพร; กาญจนสาขา, บุษบง; ละออง, สีฟ้า (วารสารวนศาสตร์ไทย, 2022)
This investigation was undertaken at Sakaerat Environmental Research Station, Nakhonratchasima province. The study site has been considered as a Biosphere Reserved Area having the total area of 81 km2 with the elevation ranging from 240 m to 760 m above mean sea level. Based on existing land use patterns, the area could be divided into 4 vegetation types as follows: dry evergreen forest (29.5 km2), dry dipterocarp forest (12.2 km2), reforested aud shifting cultivated arca (37.9 km2), and bamboo forest (1.4 kn2). Results from previous studies revealed that there were 30 species of mammals, 77 species of birds, 78 species of reptiles, and 25 species of amphibians in this arca. The current study was carried out from January to December 1987. Nests in each vegetation type were recorded together with behavior observation at least once a month along the walking transect lines. The findings showed that 33 bird species found nesting were of 13 in dry evergreen forest (Hypothymis azurea, Theron curvirostra, Nyctyornis athertoni, Copsychus malabaricus, Pellorneum ruficeps, Phaenicophaeus tristis, Pycnonotus finlaysoni, Gracula religiosa, Garrulax pectoralis, Lophura diardi, and Halcyon smyrnensis) ; 12 in dry dipterocarp forest (Dicrurus hottentotus, Dicrurus paradiscus, Megalaima lineata, Psittacula alexandri, Coracias benghalensis, Dinopium javanens, Anhene brama, Upupa epops. Francolinius pintadeanus, Centropus sinensis, Picoides canicapillus, and Gallus gallus ; and 8 in reforested and shifting cultivated areas (Lonchura punctulata, Anthus novaeseelandiae, Nectarinia jugularis, Mirafra assamica, Pycnonotus blanfordi, Prinia rufescens, Streptopelia chinensis, and Merops orientalis). Types and shapes of nests, incubation periods, eluch sizes, reproductive success, and breeding behaviors were discussed in details.